The relevance of the location of blocking highs for stratospheric variability in a changing climate - Ayarzagüena Porras, Blanca; Orsolini, Yvan J.; Langematz, Ulrike; Abalichin, Janna; Kubin, Anne (American Meteorological Society, 2015)
Previous research shows that blocking highs (BHs) influence wintertime polar stratospheric variability through the modulation of the climatological planetary waves (PWs) depending on the BH location. BHs over the Euro-Atlantic sector tend to enhance the upward PW propagation, and those over the northwestern Pacific Ocean tend to reduce it. Future changes are examined in the response of the wave activity flux to the BH location and their relationship with wintertime stratospheric variability in transient simulations of ECHAM/Modular Earth Submodel System (MESSy) Atmospheric Chemistry (EMAC). After it is verified that EMAC can reproduce qualitatively well the geographical dependence of the BH influence on PW activity injection, it is shown that this dependence does not change in the future. However, an eastward shift of the pattern of the BH influence on PW propagation over the Pacific, a farther eastward extension of the pattern over the Atlantic Ocean, and an intensification of the wavenumber-1 component of the interaction between climatological and anomalous waves are detected. Changes in the upper-tropospheric jet and an intensification of the wavenumber-1 climatological wave due to a strengthening of the Aleutian low agree with these variations. The spatial distribution of future BHs preceding extreme polar vortex events is also affected by the slight modifications in the wave activity pattern. Hence, future BHs preceding strong vortex events tend to be more concentrated over the Pacific than in the past, where BHs interfere negatively with wavenumber-1 climatological waves. Future BHs prior to major stratospheric warmings are located in a broader area than in the past, predominantly over an extended Euro-Atlantic sector. Deutscher Akademischer Austauschdienst Deutsche Forschungsgemeinschaft Research Council of Norway Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub